Research Progress and Future Development Trends in Medicinal Plant Transcriptomics - Guo, Junda; Huang, Zhen; Sun, Jialing; Cui, Xiuming; Liu, Yuan (Frontiers in Plant Science, 2021)
Transcriptomics is one of the most popular topics in biology in recent times. Transcriptome sequencing (RNA-Seq) is a high-throughput, high-sensitivity, and high-resolution technique that can be used to study model and non-model organisms. Transcriptome sequencing is also an important method for studying the genomes of medicinal plants, a topic on which limited information is available. The study of medicinal plants through transcriptomics can help researchers analyze functional genes and regulatory mechanisms of medicinal plants and improve breeding selection and cultivation techniques. This article analyzes and compares the applications of transcriptome sequencing in medicinal plants over the past decade and briefly introduces the methods of transcriptome sequencing and analysis, their applications in medicinal plant research, and potential development trends. We will focus on the research and application progress of transcriptome sequencing in the following four areas: the mining of functional genes in medicinal plants, development of molecular markers, biosynthetic pathways of secondary metabolites, and developmental mechanisms of medicinal plants. Our review will provide ideas for the mining of functional genes of medicinal plants and breeding new varieties.